BARI-IRRI Collaborative Stainable Intensification of Mixed Farming Activities and Outputs in 2023 - Ferdous, Zannatul; Hossain, Al-Amin; Alam, Robiul; Anwar, Mazharul; Khan, M. S. I.; Islam, M. M.; Ahmed, S.; Bhandari, Humnath (International Rice Research Institute, 2023)
Objectives: To provide the progress and achievement of BARI-IRRI collaborative research and scaling activities from the SI-MFS initiative in 2023.